INSIGNIFICANCE OF STOCK MARKET INVESTMENT AMONG COLLEGE TEACHERS WORKING IN THE JURISDICTION OF MANGALORE UNIVERSITY - Kumar, Yathish; Abhinandan (International Journal of Research -GRANTHAALAYAH, 2021)
The competency of a teacher is a major determinant of the quality of the education. Teacher’s professional advancement is decided by many factors. One of the main factors which strongly influence the efficiency of teacher is his quality of life. The quality of one’s life is closely related to the level consumption, savings and investment. Investments in stock market indicate high quality of life. But many research found that most of the teachers not investing in stock market. Much research done related to investment pattern of teaching faculty and investment behaviour of teaching faculty. These researches found out that teachers preferred to invest in banking investment avenues. But a less number of researches did to identify the reason for not investing in stock market avenues. Therefore this paper tries to identify the reasons for insignificance of stock market among teaching faculty. To this paper both primary data and secondary data were used. Primary data were collected through structured questionnaire and for secondary data referred various online journals and websites.